The cost-effectiveness of influenza vaccination for people aged 50 to 64 years: An international model - Aballea, Samuel (2007)
Objectives: Routine influenza vaccination is currently recommended in several countries for people aged more than 60 or 65 years or with high risk of complications. A lower age threshold of 50 years has been recommended in the United States since 1999. To help policymakers consider whether such a policy should be adopted more widely, we conducted an economic evaluation of lowering the age limit for routine influenza vaccination to 50 years in Brazil, France, Germany, and Italy.Methods: the probabilistic model was designed to compare in a single season the costs and clinical outcomes associated with two alternative vaccination policies for persons aged 50 to 64 years: reimbursement only for people at high risk of complications (current policy), and reimbursement for all individuals in this age group (proposed policy). Two perspectives were considered: third-party payer (TPP) and societal. Model inputs were obtained primarily from the published literature and validated through expert opinion. the historical distribution of annual influenza-like illness (ILI) incidence was used to simulate the uncertain incidence in any given season. We estimated gains in unadjusted and quality-adjusted life expectancy, and the cost per quality-adjusted life-year (QALY) gained. Deterministic and probabilistic sensitivity analyses were conducted.Results: Comparing the proposed to the current policy, the estimated mean costs per QALY gained were R$4,100, 13,200, 31,400 and 15,700 for Brazil, France, Germany, and Italy, respectively, from a TPP perspective. From the societal perspective, the age-based policy is predicted to yield net cost savings in Germany and Italy, whereas the cost per QALY decreased to R$2800 for Brazil and 8000 for France. the results were particularly sensitive to the ILI incidence rate, vaccine uptake, influenza fatality rate, and the costs of administering vaccination. Assuming a cost-effectiveness threshold ratio of 50,000 per QALY gained, the probabilities of the new policy being cost-effective were 94% and 95% for France, 72% and near 100% for Germany, and 89% and 99% for Italy, from the TPP and societal perspectives, respectively.Conclusions: Extending routine influenza vaccination to people more than 50 years of age is likely to be cost-effective in all four countries studied.